Beyond Individual Lives: Using Comparative Osteobiography to Trace Social Patterns in Classical Italy - Robba, John (Bioarchaeol Int, 2019)
Osteobiographical studies have usually focused upon investigating an individual’s life experience. However, we can also understand variation in the shape of the life course itself as an object of study: Are there common patterns for how lives unfold within a society? Are there events or experiences that channel life courses? This approach to the life course can be adopted for ancient as well as for modern lives. A key element here is developing new methodologies for characterizing and comparing how lives develop through time, for instance, by ordering biological data in sequence, looking for time-structured patterns in them both by eye and through multivariate statistics. This article presents an initial exploration of this problem, using skeletal and archaeological data on 47 adults from the fifth to third centuries B.C. at Pontecagnano, an urban site in Campania, Italy. The results show both the importance of gender in the life course and the effects of different kinds of physical stress, probably due to specialization in labor. The result is not discrete categories of people but fuzzy envelopes of life possibilities.